Analisis Faktor-Faktor Sikap Yang Membentuk Niat Mahasiswa Menjadi Teknopreneur - Iwan Sidharta; Rahmahwati Sidh (STMIK Mardira Indonesia, Bandung, 2013)
Analysis of Factors Forming Intentions Student Attitudes Become Technopreneur. National development can not be separated from the contribution of SMEs both in terms of employment and GDP. Empowerment of human resources quality and superior competence needs to be generated so that the achievement of national development can be accomplished. College which is the organizer of educational services required in order to produce competent human resources so that entrepreneurs employment opportunities can be created. This study aims to determine the factors that influence the attitude of entrepreneurial intention students STMIK Mardira Indonesia Bandung to be techopreneur. Exploratory research methods of data analysis techniques using Structural Equation Modelling (SEM), component-based Partial Least Squares (PLS). The number of respondents as many as 61 active students with the data collection technique with purposive sampling. Results of the study indicate where the factors positively influence the attitude of 25% on the intentions of students STMIK Mardira Indonesia, Bandung, to become technopreneur, and the influence of the biggest factors is the perceived confidence. Keywords: attitude factor; entrepreneurial intention; college; technopreur